The Early Predictive Value of Circulating Monocytes and Eosinophils in Coronary DES Restenosis - Li, Shumei; Qiu, Hong; Lin, Zhaorong; Fan, Lin; Guo, Yongzhe; Zhang, Yujie; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2022)
Background: Monocytes and eosinophils are involved in intracoronary inflammatory responses, aggravating coronary artery plaque instability and ISR. Aims: To investigate an early prediction of in-stent restenosis (ISR) in patients undergoing stenting by circulating monocytes and eosinophils. Methods: The single-center data of patients undergoing successful drug-eluting stents (DES) implantation from January 1, 2017 to April 30, 2020 were retrospectively analyzed. Of the 4,392 patients assessed, 140 restenosis patients and 141 patients without restenosis were enrolled. A scheduled postoperative follow-up was proceeded during 4 sessions: 0-3 months, 3-6 months, 6-12 months, and > 12 months. The hematological and biochemical measurement was collected. Angiographic review was completed within 2 postoperative years. Results: Significant associations of monocyte count and percentage with ISR were evident [Odds ratio (OR): 1.44, 95% confidence interval (CI): 1.23-1.68, p < 0.001; OR: 1.47, 95%CI: 1.24-1.74, p< 0.001, respectively], which began at three months post-operatively and persisted throughout the follow-up period. Eosinophil count and percentage were associated with ISR (OR: 1.22, 95%CI: 1.09-1.36, p= 0.001; OR: 1.23, 95%CI: 1.07-1.40, p= 0.003, respectively), with ISR most significantly associated with the baseline eosinophils. The receiver operating characteristic (ROC) curve analysis showed the cutoff points of monocyte count and percentage in the ISR prediction were 0.46×109/L and 7.4%, respectively, and those of eosinophil count and percentage were 0.20 ×109/L and 2.5%, respectively. Conclusion: This study, with a long-term follow-up, first evidences that the elevated monocytes at three postoperative months and baseline eosinophils may be strong early predictors of ISR after drug-eluting stent implantation. Persistent elevation of monocytes also may be a signal of ISR after PCI.